Non-Conservative Therapy in the Prevention of Subepithelial Fibroplasia after LASEK Hypermetropia Correction - S. A. Korotkikh; A. E. Bogachev; A. S. Shamkin (Oftalʹmologiâ, 2018)
The results of observation of patients who underwent vision eximerlaser correction by the LASEK method regarding medium degree of hyperopia were analyzed.Purpose: to investigate the severity of the «dry eye» syndrome and corneal subepithelial fibroplasia in patients after laser correction of  hyperopia by the LASEK method, and their prevention by reducing  the preservative action on the eye surface.Patients and methods. The study included 40 patients (76 eyes), aged 21–46 years (32.98 ± 1.79) who underwent LASEK surgery for  moderate hyperopia (4.03 ± 0.38 D). Patients were divided into two  groups: 1) control group (20 patients, 37 eyes) — postoperative  therapy included the corneoprotector “Stilavit®” and the preparation  of hyaluronic acid “Oksial®”, containing preservatives;  2) the study group (20 patients, 39 eyes) — postoperative therapy  included the corneoprotector “Hilozar-comod®” and the artificial tear  preparation “Hilo-comod®”, which did not contain reservatives. Ophthalmic examination included, in addition to standard diagnostic  methods, the Norn test, the Schirmer test, the staining of the eye  surface with lissamine green. In addition, a questionnaire was  conducted on a modified OSDI questionnaire; there a section  characterizing the quality of vision (section B) was removed.Results. The analysis of the obtained data showed that in the study group there was less pronounced “dry eye” syndrome at 3,6,12  months after the operation. The maximum difference in the  indicators of the “dry eye” syndrome between the groups was at 3  and 6 months of the postoperative period. When evaluating corneal  subepithelial fibroplasia, maximum attention was paid to the  frequency and the intensity index. It was shown a significant  difference in the intensity of the haze between the study group and the control group by 26.1 % at 3 months, by 62.2 % at 6  months and by 65.3 % 12 months after the operation. Conclusion. Nonconservative therapy with sodium hyaluronate and  dexapanthenol in the early postoperative period and only sodium  hydrolurate allows to reduce the severity of the dry eye syndrome  after laser correction of hypermetropia and, as a result, to reduce  the intensity of haze development by 65.3 %, and its frequency on 11,5 %.